The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1007/bf00162828
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and absorption of electron-cyclotron maser radiation during solar flares

Abstract: The electron-cyclotron maser is believed to be the source of microwave spike bursts often observed during solar and stellar flares. Partial absorption of this radiation as it propagates through the corona can produce plasma heating and soft X-ray emission over an extended region. In this paper, the propagation and absorption of the maser radiation during solar flares are examined through linear theory and electromagnetic particle simulations. It is shown using linear theory that strong absorption of the radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 30 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…A major ongoing difficulty with the interpretation of solar spike bursts in terms of ECME is that simple theory implies that the emission cannot escape from the solar corona, due to very strong absorption at the second harmonic layer, where the wave frequency is equal to twice the local cyclotron frequency (Melrose and Dulk 1982). There are various suggestions as to how this difficulty might be overcome (e.g., McKean et al 1989, Robinson 1989. The predicted degree of polarisation may be influenced strongly by the way this difficulty is resolved.…”
Section: (A) Expected Polarisation For Ecmementioning
confidence: 99%
“…A major ongoing difficulty with the interpretation of solar spike bursts in terms of ECME is that simple theory implies that the emission cannot escape from the solar corona, due to very strong absorption at the second harmonic layer, where the wave frequency is equal to twice the local cyclotron frequency (Melrose and Dulk 1982). There are various suggestions as to how this difficulty might be overcome (e.g., McKean et al 1989, Robinson 1989. The predicted degree of polarisation may be influenced strongly by the way this difficulty is resolved.…”
Section: (A) Expected Polarisation For Ecmementioning
confidence: 99%
“…examined the cross field transport of energy associated with the electron cyclotron maser instability. McKean, Winglee and Dulk (1989) used a numerical code to study the propagation and absoption of electron cyclotron maser radiation. They found that the bulk of the cross field energy goes into heating of the ambient plasma and a few electrons are accelerated to several KeV.…”
Section: Plasma Radiation Theories and Plasma Models Of Flare Emissionmentioning
confidence: 99%
“…One major problem of ECME when applied to solar radio bursts is about how fundamental emissions (ω ≈ Ω ce ) pass through the second-harmonic layer in the solar corona without being absorbed considerably (Melrose & Dulk 1982). Ideas suggested to circumvent the problem include: propagation through a density-depleted tunnel (e.g., Wu et al 2014;Melrose & Wheatland 2016), escape through transmission windows at θ = 0 • or 90 • (Robinson 1989, where θ is the angle between the directions of wavevector and background magnetic field), and re-emission after being absorbed by the electrons (McKean et al 1989).…”
Section: Introductionmentioning
confidence: 99%